Bacteriological Profile of Heart Valves Resected from Infective Endocarditis Patients - Manandhar, S; Basnyat, S; Sharma, J; Pokhrel, BM; Koirala, B (Journal of Nepal Health Research Council, 2010)
Background: Early prosthetic valve endocarditis is a serious life threatening infection of newly implanted prosthetic heart valve. A positive post-surgery heart valve culture is a significant risk factor for development of early prosthetic valve endocarditis. Methods: A prospective bacteriological investigation was done in intraoperatively suspected and preoperatively diagnosed infective endocarditis patients undergoing heart valve replacement surgery. The valve samples were cultured after prior homogenization by sterile scalpel method. The bacterial isolates were identified by standard microbiological techniques and their antibiotic susceptibility profile was determined in vitro by Kirby Bauer disc diffusion method. Results: Of 31 heart valve samples cultured, 3 (9.67%) were culture positive which constituted 2 (13.33%) from preoperatively diagnosed infective endocarditis patients from which Staphylococcus aureus and Enterococcus faecalis were isolated and 1 (6.25%) from intraoperatively suspected infective endocarditis patient from which Staphylococcus aureus was isolated. All three isolates were sensitive to antibiotics Vancomycin and Ciprofloxacin and resistant to Penicillin and Amoxycillin. The isolates obtained from preoperatively diagnosed patients were more resistant to antibiotics tested than that from suspected patients. Conclusions: The bacteriological examination of heart valves resected from preoperatively diagnosed and intraoperatively suspected infective endocarditis patients revealed higher degree of culture positivity. Hence routine microbiological examination of all heart valves from diagnosed and suspected IE patients is required to rule out active endocardial infection to reduce the chance of early prosthetic valve endocarditis. Key words: bacteriology; heart valves; infective endocarditis DOI: 10.3126/jnhrc.v7i2.3017 Journal of Nepal Health Research Council Vol.7(2) Apr 2009 108-111